Negative Dependencies in Turkish - Beste Kamali; Hedde Zeijlstra (Languages)
In this paper, we provide an overview of negative dependencies in Turkish. The first are elements such as hiçkimse, which sometimes seem to mean ‘anybody’ and sometimes ‘nobody’. We argue that unlike a standard Negative Polarity Item (NPI) like English anybody, these items should be analyzed as neg-words licensed under Negative Concord (NC). We also discuss further properties of these items, including whether they are universals or existentials. The second set of items that display a negative dependency are universal quantifiers such as herkes ‘everybody’. Unlike their counterparts in many languages, these items obligatorily scope under negation, which raises the question of why a universal is sensitive to negation in the way it is. We account for this behavior in terms of negative polarity sensitivity based on a referentiality requirement we dub the Non-Entailment-of-Non-Existence Condition, following a particular analysis of a class of NPIs in Mandarin. The final case of negative dependency we evaluate is modals that have to scope under or above negation. These cases constitute instances of polarity sensitivity in English and beyond, especially clearly in the case of modal PPIs. We show that in Turkish, however, they do not, and the apparent negative dependency follows from the syntax of Tense-aspect-modality (TAM) morphology.